Direct economic return to government of public geoscience information investments in Chile. (March 2018) - Gildemeister, Martin; Jara, J. Joaquín; Lagos, Gustavo; Marquardt, Carlos; Espinoza, Felipe
Abstract: This article presents the first attempt to evaluate the direct economic return of the provision of public geoscience information in Chile. To achieve this goal the study uses multiplier effect ratios through the value chain of PGI and a probabilistic discounted cash flow model to evaluate the economic returns of different scenarios for the ongoing governmental program mandated to generate country-scale geological information, named the National Geological Program. The study shows that, in average, every dollar invested in PGI in Chile during the past three decades could have generated 11.5 dollars of government tax revenues from the mining industry (in terms of its NPV), with an IRR of around 21%. These results are in accordance with comparable studies abroad, but they should be taken carefully due to methodological restrictions of the study. These indicators are positive in almost all the scenarios considered in the study, despite that they show a wide range of results. Similar outcomes are obtained for the National Geological Program when different scenarios are evaluated. Highlights: The first known attempt to evaluate the direct return to government of public geoscience information (PGI) in Chile. A general methodology, based on benefit-cost ratios through the value chain of PGI and a probabilistic DCF model, is used. Positive results are obtained (NPV/I=11.5 and IRR=21%), but they should be taken carefully due to research restrictions. Therefore, the National Geological Program should be a good public policy in terms of its economic returns to government.